1964
DOI: 10.1038/2021123a0
|View full text |Cite
|
Sign up to set email alerts
|

MK: an Apparently Silent Allele at the MN Locus

Abstract: June 13, 1%4 NATURE 1123 body to anti-Yta, the predicted anti-Ytb. This possibility was supported by the frequency of positive reactions. The specificity of the antibody was established by testing six known Yt(a-) samples, kindly supplied by Dr. M. M. Pickles, Dr. P. A. Tippett and Miss M. J. Polley, with an eluate containing only the unknown antibody in Mrs. B.'s serum. All were found to react positively. A family investigation of the original Fy(b-) Yt(b +) donor showed that her father and uncle were, in fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1969
1969
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 2 publications
1
23
1
Order By: Relevance
“…There are others still that so far have only been found in either of the two pos sible combinations: M2 and iV2 associated with a positive direct Coombs test [15,16,17,18], Ma [14] and Mz [22,23], while Mk is associated neither with S nor with s [20],…”
Section: Discussionmentioning
confidence: 99%
“…There are others still that so far have only been found in either of the two pos sible combinations: M2 and iV2 associated with a positive direct Coombs test [15,16,17,18], Ma [14] and Mz [22,23], while Mk is associated neither with S nor with s [20],…”
Section: Discussionmentioning
confidence: 99%
“…However, this is probably not the whole explanation of the delay if the tuberculin reaction can be taken as a guide. Thus Metaxas and Metaxas (1955) found that when tuberculin sensitised cells were injected intradermally together with tuberculin the characteristic delay of the tuberculin reaction was still present. The delay is thus probably in the reaction itself.…”
Section: Mechanism Of Delayed Skin Reactionmentioning
confidence: 94%
“…1 and, although the pedigree of her family has already been published elsewhere [5], to reproduce it in fig. 1 together with the pedigrees of the 5 other Mk families, which are numbered 2 to 6, in the order in which the respective propositi were found.…”
Section: The Six Mk Propositi and Their Familiesmentioning
confidence: 99%
“…The gene Mk can be recognized in the heterozygote (no homozygote has yet been found), although by quite different means than those which usually apply to blood group genes : instead of giving rise to an antigen readily defined by a specific antibody, Mk reveals its presence by a lack of antigens of the MN Ss system [5,9] and, as shown more recently [10], in other characteristics of the red cells which must be related to some abnormality of the surface of the latter. One expects such a gene to occur in half of the children of a mating in which one partner possesses it and the other does not.…”
mentioning
confidence: 99%